2017
DOI: 10.1088/1361-6528/aa8e23
|View full text |Cite
|
Sign up to set email alerts
|

The influence of atmosphere on the performance of pure-phase WZ and ZB InAs nanowire transistors

Abstract: Abstract. We compare the characteristics of phase-pure MOCVD grown ZB and WZ InAs nanowire transistors in several atmospheres: air, dry pure N 2 and O 2 , and N 2 bubbled through liquid H 2 O and alcohols to identify whether phase-related structural/surface differences affect their response. Both WZ and ZB give poor gate characteristics in dry state. Adsorption of polar species reduces off-current by 2 − 3 orders of magnitude, increases on-off ratio and significantly reduces sub-threshold slope. The key differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…Assuming an electron mobility of 210 cm 2 .V -1 .s -1 (measured in similarly synthesized samples 20 ), one can estimate that the carrier density in the nanowire to be n3x10 17 cm -3 which is also consistent with Ref. 21. Photocurrent spectra were obtained by choosing a constant current and measuring the change in the bias voltage as the laser is tuned over a wavelength range.…”
Section: Methodssupporting
confidence: 71%
“…Assuming an electron mobility of 210 cm 2 .V -1 .s -1 (measured in similarly synthesized samples 20 ), one can estimate that the carrier density in the nanowire to be n3x10 17 cm -3 which is also consistent with Ref. 21. Photocurrent spectra were obtained by choosing a constant current and measuring the change in the bias voltage as the laser is tuned over a wavelength range.…”
Section: Methodssupporting
confidence: 71%
“…Table 2 summarizes the calculated parameters for the seven multiplexed nanowires. While data points are too few for statistical comparison, it is a useful demonstration that nanowires can be successfully integrated with the multiplexer without any reduction in quality, since parameters compare favorably to nonmultiplexed WZ nanowires, 69 which showed V t = −7.4 V, on/off ratio = 3.4 dec, SS = 2320 mV dec −1 , n = 4.7 × 10 17 cm −3 , and μ FE = 340 cm 2 V s −1 . These measurements were performed at room temperature, which accounts for the lower mobility and higher SS 71 compared to our devices.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, our results are consistent with the hypothesis of a reduced carrier density in InAs NWs in the presence of air and other adsorbates, observed by Du et al The resistance of our nanowires in dry air is in fact quite higher with respect to the behavior in vacuum (see Appendix B). Ullah et al [47] also demonstrated that the adsorption of polar species, such as H 2 O and alcohols, leads to a decrease in the carrier density in the InAs channel and a decrease in the drain-source current at zero bias. The net effect observed by these authors upon exposure to N 2 or ethanol was a reduction of the drain-source current: this is consistent with our experimental outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The mentioned studies [46,47] were performed in an inert atmosphere or in a vacuum: as claimed in the same studies, inert gases do not interact at all with the surface of InAs NWs, and their effect on the sensor behavior is equivalent to the vacuum conditions. Instead, the same does not occur if the sensor is operated in air, a more appropriate environment for testing the sensor in operating conditions is closer to real life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation